Efficacy and Safety of Paracetamol for Patent Ductus Arteriosus Closure in Preterm Infants: An Updated Systematic Review and Meta-Analysis - Xiao, Yingqi; Liu, Hui; Hu, Rujun; You, Qiang; Zeng, Min; Jiang, Xiaolian (Frontiers in Pediatrics, 2020)
Background: Indomethacin and ibuprofen, two commonly used prostaglandin inhibitors, are the drugs of choice for patent ductus arteriosus. However, paracetamol is an alternative choice when these drugs are ineffective or contraindicated. This study aimed to confirm paracetamol’s efficacy and safety compared with other drugs or placebo for patent ductus arteriosus closure in premature infants. Methods: We conducted a literature search using the Cochrane Library, PubMed, CINAHL, and EMBASE databases for randomized controlled trials and quasi-randomized controlled trials. We used the PRISMA guidelines to direct the process and PICO (P: population; I: intervention/interest; C: comparator; O: outcome) principle to constitute the theme. We combined the research data through qualitative summaries or meta-analyses. Results: The final analyses included 15 trials (N = 1313). No significant differences were noted between paracetamol and ibuprofen except for shorter mean days needed for patent ductus arteriosus closure, lower risk of gastrointestinal bleeding, and hyperbilirubinemia. No significant difference existed between paracetamol and indomethacin. Oral paracetamol was more effective than placebo in infants weighing 1501–2500 g. Conclusions: Our study findings tentatively conclude that paracetamol can induce early patent ductus arteriosus closure without significant side effects but that its efficacy is not superior to that of indomethacin.